DEVELOPING AN INTERACTIVE MULTIMEDIA CD FOR ENHANCING FIFTH GRADE STUDENTS’ LISTENING COMPREHENSION (English Education Journal, 2012)
Penggunaan media sangat penting untuk mendukung proses belajar mengajar. Guru membutuhkan media yang sesuai untuk merangsang siswa menjadi aktif dan kreatif. Penggunaan media akan membantu guru dalam pencapaian hasil yang lebih baik. Studi ini menggambarkan langkah dalam pengembangan CD multimedia interaktif untuk meningkatkan listening comperhensi dan pengaruhnya pada proses belajar mengajar. Dari data dapat disimpulkan bahwa guru harus membangun materi yang digunakan pada proses mengajar karena tidak adanya materi yang sesuai, serta guru seharusnya belajar umntuk tau bagaimana mendesain dan mengembangkan materi multimedia menggunakan computer yang bervariasi karena akan member pengaruh pada proses belajar mengajar.The use of media is important to support the listening teaching and learning process. The teacher needs an appropriate media in order to make the students to be active and creative in the learning process. The use of media in the teaching and learning process will help the teacher and the students engage together to get the achievements much better and also help the students to learn by themselves. This study presents the steps in developing the interactive multimedia CD for enhancing fifth grade students’ listening comprehension and its influences on the listening teaching and learning process. The data presented suggests that teachers need to develop the material used in teaching process since not all the materials are provided and suitable with the students’ need and need to learn how to design and develop multimedia material by using various computer programs since the use of multimedia can increase students’ interest and motivation in learning process. Besides, it also can influence students’ awareness, attention, inquiry and discovery, and communication ability in the listening teaching and learning process